Ultra-processed food consumption among infants in primary health care in a city of the metropolitan region of São Paulo, Brazil, - Relvas,Gláubia Rocha Barbosa (2019)
Abstract Objective: To analyze the prevalence of ultra-processed food intake among children under one year of age and to identify associated factors. Methods: A cross-sectional design was employed. We interviewed 198 mothers of children aged between 6 and 12 months in primary healthcare units located in a city of the metropolitan region of São Paulo, Brazil. Specific foods consumed in the previous 24 h of the interview were considered to evaluate the consumption of ultra-processed foods. Variables related to mothers' and children's characteristics as well as primary healthcare units were grouped into three blocks of increasingly proximal influence on the outcome. A Poisson regression analysis was performed following a statistical hierarchical modeling to determine factors associated with ultra-processed food intake. Results: The prevalence of ultra-processed food intake was 43.1%. Infants that were not being breastfed had a higher prevalence of ultra-processed food intake but no statistical significance was found. Lower maternal education (prevalence ratio 1.55 [1.08-2.24]) and the child's first appointment at the primary healthcare unit having happened after the first week of life (prevalence ratio 1.51 [1.01-2.27]) were factors associated with the consumption of ultra-processed foods. Conclusions: High consumption of ultra-processed foods among children under 1 year of age was found. Both maternal socioeconomic status and time until the child's first appointment at the primary healthcare unit were associated with the prevalence of ultra-processed food intake.